Back to the front: Tracing reverberations of the South West African border wars of the 1970s and 1980s - Morris, Mandy Isobel (My University, 2008)
ABSTRACT This research report comprises two parts: a theoretical introduction and a creative component. The theoretical introduction explores the extensive impact of militarism in South Africa during the South West African Border Wars of the 1970s and 1980s. It also reflects on some of the literary issues that were encountered during the research period. The creative component consists of three short stories that examine some of the reverberations of living in a militarised state.
Keywords: Border War; SWA Border War